A New Graph to Display the Epidemic Outbreaks of Covid-19 in the World - Raúl Isea (International Journal of Coronaviruses, 2020)
The paper proposes a new visualization scheme for the registry of Covid-19 cases by calculating the mantissa of the registered ones, so there is no need of performing complicated mathematical calculations. As an example, six countries are randomly selected: Australia, Brazil, China, Colombia, Portugal and Venezuela. The results show that China is the only country that keeps the epidemic under control, while Australia begins a new outbreak after having previously controlled the epidemic. Colombia and Portugal show a very similar behavior of registered cases and, finally, we can see that Venezuela, Brazil, Portugal, and Colombia present a growth of cases that may trigger new outbreaks in the future. Results are obtained from data registered at Johns Hopkins University until July 18th, 2020.
Keywords: Covid-19